Analysis And Implementation of Noekeon Algorithms For Encryption and Description of Text Data - Effendi, Noverta; Fauzan Azim (Jurnal Info Sains : Informatika dan Sains, 2021)
As the times evolve, human needs increase. Including information needs. Therefore, sending and storing files through electronic media requires a process that can ensure the security and integrity of the file. To ensure the safety and integrity of a file, an encoding process is required. Encryption is performed when the file is sent. This process will convert the original file into a confidential unreadable file. Meanwhile, the decryption process is done by the recipient of the sent file. The personal file received will be converted back to the original file. By encoding, the original file will not be read by unauthorized parties but only by recipients who have a decryption key.